From credit to debt: A political history of English sovereign finance and money from the seventh century to the seventeenth - Nicolas Dorn (Finance and Society, 2019)
This article provides a new perspective on sovereign finance and money in England from pre-modern to early modern times. Re-reading the literature on sovereign fiscality through the lens of sovereign jurisdictions and religious authority, it describes two distinct forms of sovereign finance: the rise and fall of sovereign credit from the seventh to eleventh century, followed by sovereign debt developing from the eleventh century into 'modern' sovereign debt from the seventeenth century onwards. In the early Anglo Saxon period, sovereign credit was given and received in non-monetised forms. It was when sovereign jurisdictions became too wide for labour and bulky produce to travel that tax was monetised. However, the monetisation of credit undermined the very sovereign-subject relation on which sovereign credit was based. After the introduction of short-term sovereign debt by the Normans, for the next five hundred years, the two distinct fiscal mechanisms of sovereign credit and sovereign debt ran in parallel, although the latter was restrained by the church's prohibition of usury. In the seventeenth century, sovereign credit and sovereign debt became conjoined elements within one fiscal system, rather than separate mechanisms.
Keywords: 300; Pre-modern England; sovereignty; religion; war; fiscality; state theory of money